Service loading test as a source for the fatigue curve parameters’ estimation - Gadolina, I.V.; Petrova, I.M. (Проблемы прочности, 2009)
Very important question of fatigue curve parameter estimation might be explored from the point of view of service loading. Comparative testing at varied stress levels with subsequent computation might reveal some peculiarities of fatigue curves and substantial changes of their parameters due to service loading factors. Проблема определения параметров кривой усталости может быть решена с учетом особенностей эксплуатационного нагружения. Показано, что сравнительные испытания в условиях изменения уровня напряжений и учет полученных результатов в последующих расчетах позволяют определить некоторые особенности кривых усталости и существенные изменения их параметров, связанные с влиянием факторов эксплуатационного нагружения.